The secretion of the pancreas upon intraduodenal administration of trypsin and trypsin with its specific synthetic substrate (Texas Journal of Medical Science, 2023)
Earlier in our laboratory, conclusions were drawn regarding the specific substrates alleviating the selective inhibitory effects of enzymes by interacting at the catalytic center of the enzyme with the substrate. This was evidenced by data using a specific trypsin inhibitor that blocked the inhibitory effect of intraduodenally and intravenously administered trypsin (1), along with our laboratory's findings of alleviating the selective inhibition of amylase secretion by intraduodenal administration of a specific pancreatic amylase inhibitor (2). However, both protein and lipid emulsion, as substrates, exhibited elements of nonspecific enzyme sorption in their alleviating action